Bilinguisme Et Developpement Cognitif A L’ecole Primaire. Une Etude Experimentale A Partir Du Terrain Ivoirien De La Region De Bondoukou - Arsène, Seka Yapi; Christiane, Niamien (European Scientific Journal, ESJ, 2016)
Bilingualism is a subject of growing research in Ivory Coast since in many regions, there has been either a simultaneous bilingualism alternating bilingualism among school-age children. This sociological reality noted that children speak at least two local languages before school for learning French. Obviously, the young student who comes into the first primary level CM1), is facing a situation of multilingualism. From an experimental study, quantitative approach serves as a method of analysis to evaluate the effect of bilingualism among students of CM1 class of the Bondoukou region on academic performance. The study whose objective is indeed to make an analysis of the impact of bilingualism on cognitive development of learners, comes in operative assumptions. The results indicate a strong correlation between variables bilingualism, cognitive development and learning. The practice of two local languages in children proves to be an asset for cognitive development in general and learning in schools in particular. The performances by these schoolchildren in several disciplinary trials of their level, are justified in part by a good command of their native languages.